A Comprehensive Study on Pressure Die Casting: Process Mechanisms, Material Science, Challenges, and Future Trends - S. B. Pulate; S. D. Shelke; R.H. Narvade; V.R. Lawande (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Pressure Die Casting (PDC) remains a cornerstone in the mass production of complex metal components, particularly in automotive, aerospace, and electronics industries. This paper presents an in-depth analysis of the PDC process, covering fundamental mechanisms, die and alloy selection, heat transfer dynamics, defects and their mitigation, and recent innovations. The paper also discusses the integration of computational modeling, sustainability considerations, and the emergence of hybrid manufacturing systems. Through literature review and industrial case analysis, this study provides a holistic view of the current state and future directions of pressure die casting technology.
Keywords: Pressure Die Casting; Hot Chamber Die Casting; Cold Chamber Die Casting; Defects in Pressure Die Casting